THE EFFECTIVENESS OF USING ZOOM MEETINGS AND GOOGLE CLASSROOM ON LEARNING ENGLISH IN THE ERA OF THE COVID 19 PANDEMIC - Suryadi suryadi (Jurnal Bahasa Lingua Scientia, 2022)
The goal of this study was to see how effective Zoom Meetings and Google Classroom are for English language learning in the wake of the Covid 19 pandemic. A survey method is used in the research design. The data for the study was collected using a questionnaire as a data collection tool. A random sample of 53 students was chosen by adjusting the conditions, and the research objective of learning English using Zoom was less effective, with many obstacles encountered, as evidenced by analysis of survey data from respondents, but students believe that learning using Google Classroom was more effective and simple. As a result, it can be concluded that using Google Classroom is more effective and preferred by students because it did not deplete the internet. Researchers also recommend that teachers use Google Classroom for online learning during a pandemic.